A rhodol-hemicyanine based ratiometric fluorescent probe for real-time monitoring of glutathione dynamics in living cells. Issue 24 (11th November 2019) - Ren, Minghao; Wang, Linfang; Lv, Xin; Sun, Yuanqiang; Chen, Hu; Zhang, Keyuan; Wu, Qi; Bai, Yurong; Guo, Wei
Abstract : A new rhodol-hemicyanine based ratiometric and reversible fluorescent probe has been developed for real-time monitoring of glutathione dynamics in living cells. Abstract : Glutathione (GSH) plays crucial roles in various physiological and pathological processes. The fluctuation of the GSH level is closely associated with a variety of diseases and cellular functions. Hence, it is important to real-time monitor the fluctuation of GSH in living cells. In this work, we presented a rhodol-hybridized hemicyanine fluorophore (RdH ) as a selective, rapid-response, ratiometric, and reversible fluorescent probe for intracellular GSH ( t 1/2 = 89 ms, K d = 1.42 mM). The imaging assays in living cells revealed that RdH could be used to real-time monitor GSH dynamics in A549 cells under a laser scanning confocal microscope by ratiometric fluorescence changes.